2019
DOI: 10.1007/s12029-019-00292-z
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 as a Promising Marker for Radioresistance in Colorectal Cancer

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Niclosamide is an FD-approved Wnt inhibitor that suppresses CSCs populations ( Park et al, 2019 ). Niclosamide, originally indicated for tapeworm infection, has anticancer effects in treating colorectal cancer, and DCLK1 inhibition might overcome radioresistance in CRC ( Wu et al, 2020a ; Mohammadi and Najafi 2020 ). Nintedanib inhibits VEGFR kinase activity, directly decreasing tumor growth and shrinkage ( Hilberg et al, 2018 ).…”
Section: Methods To Knockdown Dclk1mentioning
confidence: 99%
“…Niclosamide is an FD-approved Wnt inhibitor that suppresses CSCs populations ( Park et al, 2019 ). Niclosamide, originally indicated for tapeworm infection, has anticancer effects in treating colorectal cancer, and DCLK1 inhibition might overcome radioresistance in CRC ( Wu et al, 2020a ; Mohammadi and Najafi 2020 ). Nintedanib inhibits VEGFR kinase activity, directly decreasing tumor growth and shrinkage ( Hilberg et al, 2018 ).…”
Section: Methods To Knockdown Dclk1mentioning
confidence: 99%
“…DCLK1 plays a critical role in injury response for repair via regulating DDR [8]. However, recently the role of DCLK1 in the regulation of DDR in cancers has established by many investigators [66][67][68]. In an in vitro mechanistic study, it is reported that DCLK1 caused chromatin instability, and chromatin rearrangement in colon, lung, and breast cancer cell lines, which drives the advancement of cancer cells for progression and this function is independent of its kinase activity [68].…”
Section: -[58])mentioning
confidence: 99%
“…Therefore, DCLK1 probably is a potential therapeutic target to overcome chemoresistance. 42 However, the mechanisms of DCLK1-promoting chemoresistance remains not fully understood. Especially, the relationship between DCLK1, chemoresistance and tumour stem cells needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that LRRK2‐IN‐1 (a nonspecific selective inhibitor of DCLK1) enhanced the cytotoxic effects of gemcitabine via suppressing Chk1 phosphorylation in pancreatic cancer cells. Therefore, DCLK1 probably is a potential therapeutic target to overcome chemoresistance 42 . However, the mechanisms of DCLK1‐promoting chemoresistance remains not fully understood.…”
Section: Introductionmentioning
confidence: 99%